The 3D OrbiSIMS—label-free metabolic imaging with subcellular lateral resolution and high mass-resolving power - Passarelli, Melissa K.; Pirkl, Alexander; Moellers, Rudolf; Grinfeld, Dmitry; Kollmer, Felix; Havelund, Rasmus; Newman, Carla F.; Marshall, Peter S.; Arlinghaus, Henrik; Alexander, Morgan R.; West, Andy; Horning, Stevan; et al. (Nature Publishing Group, 2017)
We report the development of a 3D OrbiSIMS instrument for label-free biomedical imaging. It combines the high spatial resolution of secondary ion mass spectrometry (SIMS; under 200 nm for inorganic species and under 2 μm for biomolecules) with the high mass-resolving power of an Orbitrap (>240,000 at m/z 200). This allows exogenous and endogenous metabolites to be visualized in 3D with subcellular resolution. We imaged the distribution of neurotransmitters—gamma-aminobutyric acid, dopamine and serotonin—with high spectroscopic confidence in the mouse hippocampus. We also putatively annotated and mapped the subcellular localization of 29 sulfoglycosphingolipids and 45 glycerophospholipids, and we confirmed lipid identities with tandem mass spectrometry. We demonstrated single-cell metabolomic profiling using rat alveolar macrophage cells incubated with different concentrations of the drug amiodarone, and we observed that the upregulation of phospholipid species and cholesterol is correlated with the accumulation of amiodarone.